Studi subtitusi tepung tapioka dengan tepung maizena terhadap kualitas fisik kamaboko ikan Belut (Synbrancus bengalensis) - Tyas Wara Sulistyaningrum; - Norhayani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
The purpose of this study is to obtain innovative diversified products that are highly nutritious with the physical quality that can be recommended. The research activities include physical test by using folding test. Folding test is one of the test of fish gel quality (Kamaboko) which is done by cutting the sample with a thickness of 3 mm. The sample pieces are placed between the thumb and forefinger, than folded to observe wheter or not there is a crack in the fish gel (Kamaboko). Testing conducted by 10 panelists. In this study using the 4 treatment such as : Treatment O without the addition of corn starch (control) + tapioca flour 10 %, treatment A with addition of corn starch 2 % + tapioca flour 8 %, treatment B with addition of corn starch 6 % + tapioca flour 4 %, and treatment C with addition of corn starch 10 %. The highest folding test value is in the treatment A with the composition of corn starch 2 % and tapioca flour 8 %. Key words : Kamaboko, eel fish, tapioca flour, corn starch